EVALUASI PERHITUNGAN PAJAK PENGHASILAN PASAL 21 PEGAWAI TETAP PT. BANK SULUTGO KANTOR PUSAT MANADO - Hendra Wati Bukidz (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2022)
Income Tax is a tax imposed on a tax subject on income received or earned in one tax year. Income Tax is imposed on income in the form of salaries, wages, honorarium, allowances and other payments under any name in connection with the work, services or activities carried out by the taxpayer. This study aims to determine the calculation of Income Tax (PPh) Article 21 Permanent Employees of PT. Bank SulutGo Manado Head Office. This type of research is qualitative research. The research method used is descriptive analysis method. The results showed that the calculation of Income Tax Article 21 at PT. Bank SulutGo Manado Head Office has not fully complied with the tax regulations of Law Number 36 of 2008 concerning Income Tax. PT. Bank SulutGo Manado Head Office was found to be less careful in paying attention to employee status and calculating Article 21 Income Tax on the income of permanent employees, resulting in overpayments that were detrimental to employees and the company.